PERANCANGAN SISTEM INFORMASI PENGELOLAAN TUGAS AKHIR BERBASIS ANDROID JURUSAN TEKNIK ELEKTRONIKA UNP - Claudia Gusra; Ahmaddul Hadi (Universitas Negeri Padang, 2019)
At present technology development is almost thoroughly in all circles and fields. One area that cannot be separated from technology is the field of education. It is well known that the development of cellular technology is increasing rapidly, because with a smartphone it can do many things to run mobile applications so that it can easily obtain and process information data. The purpose of this design is to build an information system using the concept of Android-based technology, so that it can serve the process of managing college student final assignments online whenever and wherever they are. The design of this final project management information system is designed using the programming language PHP (Hypertext Preprocessor) with the CodeIgniter Framework, JavaScript, and using the MYSQL database. With this system, it can help the management process of the final assignment from submitting the final assignment proposal to the trial exam for college student who have fulfilled the academic requirements with administration, academic counselors, study program chairman, mentors, and head of program.Keywords: Information System, PHP, CodeIgniter, MySQL, Android